Reviewer Acknowledgements for Journal of Agricultural Studies, Vol. 11, No. 3 - Williams, Richard (Journal of Agricultural Studies, 2023)
Journal of Agricultural Studies (JAS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JAS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 11, Number 3 Angel Ramon Sanchez Delgado, Universidade federal Rural do Rio de Janeiro, Brazil Arnaud Z. Dragicevic, IRSTEA, France Azwimbavhi Reckson Mulidzi, Agricultural Research Council, South Africa Habu Saleh Hamisu, National Horticultural Research Institute, Nigeria Jorge A. López, University Tiradentes, Brazil Juliana Nneka Ikpe, Akanu Ibiam Federal Polytechnic, Nigeria Toncho Gospodinov Penev, Trakia University, Bulgaria Richard Williams Editorial Assistant Journal of Agricultural Studies ————————————– Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Phone: 1-702-953-1852 ext.521 Email 1: jas@macrothink.org Email 2: jas@macrothink.com URL: http://jas.macrothink.org